Eliminating iodine deficiency disorders: the role of the International Council in the global partnership - Hetzel Basil S. (Bulletin of the World Health Organization, 2002)
ABSTRACT: Iodine deficiency is the most common preventable cause of brain damage. WHO estimates that some 2.2 billion people are at risk from iodine deficiency in 130 countries. A programme of universal salt iodization was established in 1994 with the aim of eliminating the problem by 2000. This paper reports progress in this field, with particular reference to the primarily scientific role of the International Council for Control of Iodine Deficiency Disorders, a nongovernmental organization founded in 1986. It is now a multidisciplinary network of 600 professionals in 100 countries.